A clínica psicanalítica frente à tradição médico-pisquiátrica - Werneck, Marina Bezerra (2025)
This dissertation investigates the constitution of psychoanalytic clinical practice in relation to the medical-psychiatric tradition. Freud’s founding of psychoanalysis is preceded by the clinical impasse posed by hysteria, whose etiology and treatment proved inaccessible to neurology and the anatomo-clinical paradigm. Faced with the insufficiency of prevailing medical models, Freud enacts an epistemological rupture by postulating the existence of the unconscious, inaugurating psychoanalysis as a clinical and theoretical method to address neurotic symptoms. Similarly, Lacan makes a decisive turn toward psychoanalysis through his critique of psychiatry, especially organicist doctrines and the lack of consistent therapeutic perspectives in treating psychoses. Throughout his trajectory, Lacan revisits Freud’s work, supported by contributions from other fields, formulating original concepts and promoting a structural reinterpretation of the Oedipus complex. While Freud places the paternal function at the center of neurosis and culture, Lacan radicalizes this function in the theory of foreclosure of the Name-of-the-Father as the structural axis of psychosis. This research thus aims to trace this theoretical development through an epistemological problematization of medicine, distinguishing neurology and psychiatry in the authors’ paths, and emphasizing the centrality of the Oedipus complex and the paternal function as articulations between psychic suffering and the symbolic dimension of culture. This debate proves particularly relevant in the contemporary context of psychopathology, marked by the dominance of the technoscientific and biologizing discourse of the DSM-5